PATTERNS OF LEARNING THE QURAN IN MERATUS HEARTLAND: CHALLENGES AND SOLUTIONS - Fadil, Muhammad Ihsan; Nida, Najminnur Hasanatun; Putera, Agustian Ramadana (UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
The teaching and learning process at Pondok Al-Quran Ar-Raudhah Tilahan, a learning institution in rural Meratus, uses traditional learning patterns that combine the Iqro' method with the sorogan method, demonstration method, and drill method. Although there are some internal issues with the students and external issues with the inadequate conditions in rural Meratus, this learning pattern is considered successful in producing students with good Quranic reading skills. This study was conducted using a qualitative approach and data collection techniques through observation, interviews, and documentation, as well as qualitative descriptive data analysis. This writing is expected to provide an overview of the reality of learning in rural areas and various alternative solutions for existing learning challenges.